2019
DOI: 10.1098/rsob.180212
|View full text |Cite
|
Sign up to set email alerts
|

Emerging microRNA biomarkers for colorectal cancer diagnosis and prognosis

Abstract: MicroRNAs (miRNAs) are one abundant class of small, endogenous non-coding RNAs, which regulate various biological processes by inhibiting expression of target genes. miRNAs have important functional roles in carcinogenesis and development of colorectal cancer (CRC), and emerging evidence has indicated the feasibility of miRNAs as robust cancer biomarkers. This review summarizes the progress in miRNA-related research, including study of its oncogene or tumour-suppressor roles and the advantages of miRNA biomark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(65 citation statements)
references
References 142 publications
0
64
0
1
Order By: Relevance
“…Several studies have shown that miRNAs was involved in the development and metastasis of various cancers, and plays an important role in tumorigenesis and homeostasis [17] , [18] . In recent years, many literatures pointed out that miRNAs can be used as a biomarker for cancer or tumors in the diagnosis and prognosis of breast cancer [19] , ovarian cancer [20] , gastric cancer [21] , and colorectal cancer [22] . Peripheral blood miRNAs may be derived from the lysis of apoptotic tumor cells, blood cells, macrophages, etc [23] .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that miRNAs was involved in the development and metastasis of various cancers, and plays an important role in tumorigenesis and homeostasis [17] , [18] . In recent years, many literatures pointed out that miRNAs can be used as a biomarker for cancer or tumors in the diagnosis and prognosis of breast cancer [19] , ovarian cancer [20] , gastric cancer [21] , and colorectal cancer [22] . Peripheral blood miRNAs may be derived from the lysis of apoptotic tumor cells, blood cells, macrophages, etc [23] .…”
Section: Introductionmentioning
confidence: 99%
“…3 Many studies demonstrate that miRNA expression changes significantly in various tumors, making it as biomarkers for tumor diagnosis, subclassify, and prognosis prediction. [4][5][6] More importantly, the changed miRNAs play very important roles in the process of tumorigenesis, development, and progression. [7][8][9] It has been also found that miRNA expression is dysregulated in NPC, [10][11][12] and the dysregulated miRNAs can promote NPC cell proliferation, invasion, and angiogenesis, including miR-125b, miR-506, miR-142-3p, miR-23a, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Given the advancement in the "high-throughput genome-wide profiling" and "screening technologies", newly emerged miRNA signatures and several "miRNA-mRNA" crosstalk have been identified in CRC 21 . An example of those signatures is the MIR34A gene expression, which plays a critical role in all stages of colorectal carcinogenesis, starting from colon epithelium proliferation, dysplasia, early/late adenoma, and progression to malignant neoplasm (Fig.…”
Section: Discussionmentioning
confidence: 99%